On trusting God: The Nicene Creed’s opening sentence - van den Brink, Gijsbert (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
This research explores the meaning of the first article of the Nicene Creed (‘We believe in one God, the Father Almighty, Maker of all things visible and invisible’) in an attempt to interpret each word and phrase within the Creed’s historical context. It then highlights the abiding relevance of this article in light of contemporary challenges, examining how the Creed continues to provide theological orientation in a culture that questions belief in one God, critiques the traditional divine attributes of fatherhood and almightiness, and faces the ecological consequences of neglecting (the non-human parts of) God’s creation. Contribution: This research argues, in particular, that the Creed portrays God as the one in whom humans can place unconditional trust.